The Role of Monks and the Governance: บทบาทพระสงฆ์กับการเมืองการปกครอง - Rodkaew, Montree (Journal of Graduate MCU KhonKaen Campus, 2022)
This academic article is aimed to present the role of the monks and the governance in Thai society. Hence, the role of monks refers to the guidelines of behaviors in Theravada Buddhist Disciplines that is different from laymen. The role and the significance of monks, which is in an individual status and organization, can be analyzed from the relationship between the monks and rulers as well as the population since the Sukhothai Period. The monks have played their roles in the duty of King’s counselors. Sometimes, they could present their choices of decision to a King pertaining to a country’s governance as it could be seen during the reign of King Ramkhamhaeng, King Phayalithai, and King Narai The Great. In the present times, the government and political leaders in Thailand who are Buddhists, have wholeheartedly attempted to adapt the Buddhist teachings to show fairness in politics. It is a condition for most of the people of the country to live together with harmony